MODEL PENGELOLA ZAKAT UNTUK MENGATASI KEMISKINAN DI KOTA BIMA - HAMIDY THALIB; MUHAMMAD IRWAN; IHSAN RO’IS (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". This study aims to determine how the zakat management model in Bima City. This study used descriptive qualitative method. The results of the research are: how to manage amil zakat there in accordance with Islamic principles, and is not in accordance with Islamic principles.